COMMUNICATIVE INSTRUCTION BASED ON LISTENING APPROACH: A RESEARCH AT THE INDONESIAN IMMERSIVE ENVIRONMENT - Widya Rizky Pratiwi; Bachtiar Bachtiar (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2023)
Creative Innovation in teaching significantly impacts EFL students' success. Thisresearch explored teachers' teaching methods in an Indonesian English immersiveEnvironment. It was a qualitative study that involved eight participants. Theresearch was conducted in a "Let's Speak class" at Mr. Pepsi Upgrade EnglishInstitution in Kampung Inggris Pare, Kediri. Data were collected from classroomobservation, interviews, photos, and documents. Then, the data were analyzed insix steps, from preparing to interpreting the description of the data's meaning.Research findings presented that teacher in Indonesian immersive environmentstaught English, especially for communicative instruction, utilizing technology, suchas communicative instruction based on a listening approach. It was called aListening-based Communicative Instructional Approach model (L-CIA model). Sixphases were trained, from giving ice-breaking preface and chitchat, listening to asong and filling in the blank, finding problematic words and translating, explainingthe song using own words, and singing together. This method has been proven tostimulate the students' speaking skills. Finally, this research contributed to sharinginformation about teaching Innovation in Second Language Acquisition in theIndonesian Immersive Environment, which can be implemented in other contexts.